Excelling in Sport Psychology : planning, preparing, and executing applied work - Pope-Rhodius, Alison (New York : Routledge, 2018)
"Written for graduate students and early professionals who are conducting applied sport psychology work for the first time, Excelling in Sport Psychology is a guide for planning, preparing, and executing this work. Each chapter addresses a critical component of the internship experience, such as selecting a site for an internship, preparing to begin the work, evaluating the completed work, and marketing oneself throughout one's early career. The diverse experiences of the various authors provide a range of viewpoints for trainees to consider and apply to their growth as a sport psychology or mental skills professional. The text is written in a practical manner, with suggestions and questions that will drive this personal and professional growth. Each chapter also includes a personal account from a current student or recent graduate about their experience in that area. This book will appeal to students in academic sport psychology programs seeking additional support and guidance about the internship process, as well as post-graduates who did not have an internship component to their program. Supervisors will benefit from reading the book as it highlights ways to work with trainees. Drawn from the experience of the applied Sport Psychology department at John F. Kennedy University, which has helped students set up internships, have successful experiences, and attain jobs for over 25 years, this book can provide a model for training programs approaching the challenges of fieldwork."--Provided by publisher.
chapter 1 Pursuing Applied Work -- Are You Ready? / Alison Pope-Rhodius Sara Robinson Sean J. Fitzpatrick -- chapter 2 Securing an Internship Site -- Where in the World Are You Going? / Deborah Munch Andre Demian -- chapter 3 Finding a Supervisor -- How Can You Create the Right Match? / Victoria Tomlinson Brian Alexander -- chapter 4 Acknowledging Biases -- How Can Who You Are Affect What You See? / Michelle Bartlett Zane Winslade -- chapter 5 Developing Self-Awareness -- Have You Ever Looked in the Mirror? / Meg Kimball-Hodges Perri Ford -- chapter 6 Working with Your Supervisor -- What, You Have Another Relationship to Think About? / Alison Pope-Rhodius Michael Howard -- chapter 7 Doing the Work -- Can You Go from the Classroom to the Field? / Megan Byrd Noelle Menendez -- chapter 8 Collaborating -- Are You a Team Player? / Tyson Holt Daniery Rosario -- chapter 9 Being Your Best -- Are You Looking After Yourself? / Sara Robinson Alexsandra Walton -- chapter 10 Ethical Quandaries -- What Were You Thinking? / Hillary Cauthen Amber M. Shipherd -- chapter 11 Handling Referrals -- What If Your Clients Need More? / C.A. Gajus-Ramsay Michael-Thomas Wilson -- chapter 12 Evaluation -- You Think You$1 (Bre Good, but Do You Really Have Any Idea? /s Sean J. Fitzpatrick Spencer Ingels -- chapter 13 Reaching the Finish Line -- r
Keywords: Psychology, Applied; Sports -- Psychological aspects